DALIT THEOLOGY: VOICE OF THE OPPRESSED: . - Madtha, William (Journal of Dharma, 1991)
Today, two of the most urgent questions that face any religion are the questions of the many poor and many religions. 1 The answers that the churches, Christian as well as non-christian, give to these challanges will determine their relevance. In this context, when religions of different view points dialogue together on the poor a fruitful arid critical reflection, rooted in theo-praxis, will emerge. Such praxis and dialogue-based reflection! on dalit situation may be provisionally ch ristened as dalit theology.